Model Kepatuhan Wajib Pajak (Studi pada Wajib Pajak yang Melakukan Usaha di Kota Medan) - Dahrani Dahrani; Maya Sari; Fitriani Saragih; Jufrizen Jufrizen (Jurnal Akuntansi dan Pajak, 2021)
This study aims to produce a Taxpayer Compliance model (Study on Taxpayers Doing Business in Medan City. The research was conducted in Medan City. The population of this study is taxpayers who carry out business activities in Medan City, both individual taxpayers and businessmen. corporate tax. Because the number of taxpayers who carry out activities in Medan City is very large and the population is unknown, a sample selection was made and 97 taxpayers were obtained. The sample selection was taken by convenience sampling technique. The survey used a media questionnaire (questionnaire). The data analysis technique used was descriptive statistical analysis and SEM-PLS with Smart PLS software. The results showed that there was a significant positive effect of procedural justice on Taxpayer Compliance. There was a significant positive effect of norms. per sonal on Taxpayer Compliance. there is a significant positive effect of procedural justice on personal norms. Moderation of Trust in Tax Authorities is able to strengthen the effect of procedural justice on Taxpayer Compliance